2019
DOI: 10.3846/jau.2019.6057
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Concepts of Cultural Heritage Village Toward a Tourism Development; A Case Study of Kadilangu Demak Indonesia

Abstract: Globalization perspective considers the world as a large market, which requires the resources readiness as capital to be able to participate actively. Local culture is an important capital to create identity and social harmonization in constructing a better quality of life. In the 15th–16th century AD, the Java north coast of Indonesia was known for having several old towns with their important roles in spreading Islam. Centuries later the legend of Walisanga still greatly influences the people’s lives particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Local culture is a capital to enhance local economy through creativity (Catungal et al, 2009;Collins & Fahy, 2011;Escalona-Orcao et al, 2016;Florida, 2003;Grodach, 2017;Hall, 2000;Kakiuchi, 2016;Ojha, 2017;Sasaki, 2010;Suprapti et al, 2019). Suprapti et al (2019) mentioned that local culture is potential to emerge the creative economy in a cultural village. Local culture stimulates the emergence of the creative economy and productive space.…”
Section: Discussion: Creative Urban Kampung Conception On Kampung Busmentioning
confidence: 99%
See 3 more Smart Citations
“…Local culture is a capital to enhance local economy through creativity (Catungal et al, 2009;Collins & Fahy, 2011;Escalona-Orcao et al, 2016;Florida, 2003;Grodach, 2017;Hall, 2000;Kakiuchi, 2016;Ojha, 2017;Sasaki, 2010;Suprapti et al, 2019). Suprapti et al (2019) mentioned that local culture is potential to emerge the creative economy in a cultural village. Local culture stimulates the emergence of the creative economy and productive space.…”
Section: Discussion: Creative Urban Kampung Conception On Kampung Busmentioning
confidence: 99%
“…Local cultures provide opportunities for creating urban innovations in social, cultural, and political (Kagan et al, 2018), as well as in urban kampung. Suprapti et al (2019) revealed that local cultures are the capitals for villages to improve their economic activity, such as by tourism activity. Necissa (2011) also argued that cultural heritage activity has economic benefits to local economic development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inline with that above, Oikonomopoulou et al (2017) convey that digitalization of technology is needed to support the preservation efforts. (Suprapti et al, 2019;Umar et al, 2019). They also show intangiblecultural values.…”
Section: Toward Sustainable Preservation Of 'Omah Pencu'mentioning
confidence: 99%